Growth divergence and income inequality in OECD countries: the role of trade and financial openness - Enrico D'Elia; Roberta De Santis (London School of Economics and Political Science (LSE), European Institute, 2019)
This paper analyses trade and financial openness effects on growth and income inequality in 35 OECD countries. Our model takes into account both short run and long run effects of factors explaining income divergence between and within the countries. We estimate, for the period 1995-2016, an error correction model in which per capita GDP and inequality are driven by changes over time of selected factors and by the deviation from a long run relationship. Stylised facts suggest that trade and financial openness reduce the growth gaps across the countries but not income inequality, and the effects of finance are stronger in high income countries. Nevertheless, low and middle income countries benefit more from international trade. Our contribution to the existing literature is threefold: i) we study the short and long run effects of trade and financial openness on income level and distribution, ii) we focus on developed countries (OECD) rather than on developing and iii) we provide a sensitivity analysis including in our baseline equation an institutional indicator, a trade agreement proxy and a dummy of global financial crisis. Estimates results indicate that trade openness significantly improved the conditions of OECD low income countries both in short and long run mostly, consistently with the catching up theory. It also decreased inequality, but only in low and middle income countries. Differently financial openness had a positive and significant impact only in the short run on middle income countries and increased income disparities within countries in the short term in low income countries and in the long term in high income countries.
Keywords: 330; Trade openness; income inequality; panel data analysis